Ageing, death and life satisfaction: evidence from the HILDA Survey. - Wooden, Mark; Li, Ning (My University, 2016)
Does subjective well-being rise or fall with age or are most people, especially those in old age, sufficiently resilient that levels of subjective well-being are very stable over the life course? This article uses longitudinal data from the Household, Income and Labour Dynamics in Australia Survey and finds that self-reported life satisfaction among a large sample of Australians does vary over time. Nevertheless, over much of adulthood—between ages 25 and 65 years—the range in this variation is very small. As people enter old age, however, life satisfaction falls quite sharply. Furthermore, this fall does not appear to be entirely driven by mortality, with the decline beginning many years prior to death.
Australian Economic Review
Keywords: Ageing; Health and wellbeing